2007
DOI: 10.1093/humrep/del514
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of side-population cells in human normal endometrium

Abstract: BACKGROUND: It has been proposed that the human endometrium may contain a population of adult stem cells that are responsible for its remarkable regenerative capability. Recently, a subset of stem cells or progenitor cells in adult tissue has been identified as side-population cells (SP cells) displaying low staining with Hoechst 33342 by fluorescenceactivated cell sorter (FACS) analysis. In this study, we isolated SP cells from the human endometrium and analysed their properties. METHOD: Endometrial cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
198
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 27 publications
(31 reference statements)
7
198
1
1
Order By: Relevance
“…Still, others have identified SP cells in benign endometrium. 31 Interestingly, while the SP fraction was enriched in the CD9 -, CD13 -cell sub-population, the SP cells could give rise to CD9 + gland-like cells and CD13 + stromal cells. 31 It is not clear, however, whether or not there are multiple classes/gradations of stem/progenitor cells that can give rise to the glandular epithelium and stromal cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Still, others have identified SP cells in benign endometrium. 31 Interestingly, while the SP fraction was enriched in the CD9 -, CD13 -cell sub-population, the SP cells could give rise to CD9 + gland-like cells and CD13 + stromal cells. 31 It is not clear, however, whether or not there are multiple classes/gradations of stem/progenitor cells that can give rise to the glandular epithelium and stromal cells.…”
Section: Discussionmentioning
confidence: 95%
“…Data from a more recent study that identified SP and non-SP populations in benign endometrium suggests that stem/progenitor endometrial cells may give rise to both epithelial and stromal cells 31 and implicates a more endogenous source. We assessed the cellular phenotype of cells derived from a serially transplanted tumor by flow cytometry analysis of the expression of Ep-CAM, an epithelial marker.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell subpopulations with the features of stem cells have been detected in a number of mammalian species, including humans, using the fluorescent stain Hoechst 33342 and these minor populations are termed side population (SP) cells (Goodell et al 1996). Further, Kato et al (2007) have isolated such cells from human endometrium and showed that they can be categorized as progenitor cells because they can differentiate into epithelial and stromal endometrial cells. Cervello et al described a population of label-retaining cells (LRCs) in mouse endometrium which express markers specific for undifferentiated cells -c-kit and pou5f1 (Chan & Gargett 2006, Cervello et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…We have isolated SP cells from normal human endometrium and from a human endometrial cancer cell line, Hec1, and characterized their properties (28,29). We have shown that Hec1-SP cells have cancer stem-like cell features.…”
Section: Introductionmentioning
confidence: 99%